Enhancing Community Satisfaction at Bukittinggi Polresta: The Interplay of Service Quality, Trust, and Institutional Reputation - Fitria Fitria; Perengki Susanto (STIE AMKOP, 2023)
The objective of this study was to examine the relationship between service quality and trust on community satisfaction. The study involved a total population of 1,600 individuals, with a sample size of 110 people. Data was collected through the distribution of questionnaires that utilized a Likert scale model. The validity and reliability of the questionnaire were assessed. The data analysis technique employed in this study was the Smart PLS method. The findings of the study are as follows: a) Service quality was found to have a positive and significant impact on community satisfaction at the Bukittinggi Police Station, b) Community trust was found to have a positive and significant influence on community satisfaction at the Bukittinggi Police Station, c) Institutional reputation was found to have a positive and significant influence on community satisfaction at the Bukittinggi Police Station, d) The quality of service was not found to be moderated by the institutional reputation variable in relation to community satisfaction at the Bukittinggi Police Station, e) Public trust was not found to be moderated by the institutional reputation variable in relation to community satisfaction at the Bukittinggi Police Station. In summary, the study identified significant positive relationships between service quality, community trust, and institutional reputation with community satisfaction at the Bukittinggi Police Station. However, the analysis did not find evidence to support the moderation effects of institutional reputation on the relationship between service quality and community satisfaction, or between public trust and community satisfaction at the police station. Keywords: Quality of Service, Public Trust, Institutional Reputation, Community Satisfaction